Identification and characterization of hematopoietic stem cells from the yolk sac of the early mouse embryo. - Huang, H (1993)
The yolk sac is the first site of hematopoiesis in the mammalian embryo. However, little is known about the initial stem cells in the yolk sac. We have isolated hematopoietic stem cells from early mouse embryonic yolk sac by using a sequential protocol of nonadherence to plastic, density gradient centrifugation, immunocytoadherence, and cell sorting. Isolated, nonadherent, density < 1.077-g/cm3, surface antigen AA4.1+, wheat germ agglutinin bright (WGAbright) cells give rise to multiple lineages, including T cells, B cells, and myeloid cells, as detected by using fetal thymus organ culture, S17 stromal feeder layers, or methylcellulose culture colony-forming cells, respectively. AA4.1+, WGAbright cells expressed high levels of heat-stable antigen (HSA) and CD45 (Ly-5) but did not significantly express major histocompatibility complex antigens, CD44, or Sca-1. Peak stem cell concentration is reached by day 11, before stem cells can be found in the liver, omentum, or thymus. In vivo long-term reconstitution of lethally irradiated mice was effected by as few as 720 AA4.1+, WGAbright yolk sac cells, but it required addition of a subset of bone marrow cells capable of providing immediate (short-term) radiation protection. Yolk sac donor-derived T cells, B cells, and macrophages were readily identified 6 months after transfer of yolk sac-derived stem cells. We suggest that, because of their cell surface phenotype as well as their capacity to differentiate in vitro and in vivo, the cells isolated from the mouse embryonic yolk sac may include the most primitive hematopoietic pluripotential stem cells yet identified.